Vitamin C supplementation on growth performance and gonadal development in Nile tilapia - Martins, Tamyres Pereira Araújo; Gomides, Pedro Fellipe Vieira; Navarro, Fernanda keley Silva Pereira; Navarro, Rodrigo Diana (Acta Scientiarum. Technology, 2016)
The study aimed to verify the vitamin C supplementation on performance and gonadal development of Nile tilapia. 160 fingerlings distributed in 16 tanks with 65 L capacity and constant water renewal in a closed recirculation system were used. The design was completely randomized with four treatments (0, 150, 300, and 600 mg of monophosphate L-ascorbic acid kg-1 diet) and four replications. We evaluated the weight gain parameters, apparent feed conversion, apparent feed intake and carcass yield to evaluate of production performance. We analyzed the sexual maturation stage and gonadosomatic index (GSI) to evaluate reproductive performance. There was no statistical difference in the performance parameters. It was observed significant difference to the GSI. No significance was found regarding other reproduction parameters. We recommend the use of 150 mg kg-1 of vitamin C to the diet of Nile tilapia from to the reproductive index. Â